β-Hydroxybutyrate, One of the Three Main Ketone Bodies, Ameliorates Acute Pancreatitis in Rats by Suppressing the NLRP3 Inflammasome Pathway - Şahin, Erhan; Bektur Aykanat, N. Ezgi; Kacar, Sedat; Bagci, Rıdvan; Sahinturk, Varol (Turkish Journal of Gastroenterology, 2021)
Background: Acute pancreatitis (AP) is a widespread disease resulting from the inflammation of acinar cells in the pancreas.β-hydroxybutyrate (BHB) is a water-soluble main ketone body synthesized in the human liver. The purpose of this study was to examinethe possible therapeutic effects of BHB in the experimentally-induced AP model in rats.Methods: In our study, male rats were randomly allotted into 6 groups, as control (0.9% saline i.p.), BHB1 (200 mg/kg BHB i.p.), BHB2(2 doses of 200 mg/kg BHB i.p.), AP (4 doses of 50 μg/kg cerulein i.p., 4 doses at 1 h intervals), AP+BHB1 and AP+BHB2 groups. In pancreatictissue sections, immunohistochemistry staining and western blot analysis for the inflammasome complex (caspase-1, ASC, andNLRP3) and inflammation-associated proteins (TNF-α and NF-κB) and a histopathological examination were performed. The levels oflipase, amylase, interleukin (IL)-18 and IL-1β in serum were measured.Results: Several pathological degenerations, including edema, inflammatory cell infiltration, acinus necrosis, and bleeding were observedin the AP group, while the histological architecture of the control and the sham BHB1 and BHB2 groups were regular. The AP-inducedpathological changes were considerably alleviated in the AP+BHB1 and AP+BHB2 groups. In the AP group, a conspicuous increase incaspase-1, ASC, NLRP3, TNF-α, and NF-κB proteins, and in the levels of amylase, lipase, IL-18, and IL-1β were detected. BHB treatmentsafter AP induction decreased those proteins to the level of control.Conclusions: We demonstrated that BHB has the potential to cure AP by suppressing the NLRP3 inflammasome and can be used in thetreatment of many diseases which progress through the NLRP3 inflammasome.